1981
DOI: 10.1002/pros.2990020310
|View full text |Cite
|
Sign up to set email alerts
|

Cyproterone acetate, testosterone, LH, FSH, and prolactin levels in plasma after intramuscular application of cyproterone acetate in patients with prostatic cancer

Abstract: Five patients with prostatic carcinoma (stages T3N0M0) were injected intramuscularly with 300 mg of cyproterone acetate (CPA) (Androcur-Depot) at weekly intervals. The concentrations of CPA, testosterone, LH, FSH, and prolactin in plasma after the first, third, and fifth injection were measured by specific radioimmunoassays. After five injections of Androcur-Depot, CPA levels were slightly higher than in previous determinations, suggesting that a balance between active substance release from the depot and excr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Lower doses of estrogen produce tumor regression without cardiovascular complications but may be less effective than castration. Progestational agents alone are only transiently effective at reducing testosterone (5,6), whereas the recent introduction of antiandrogens (7) or combination of estrogen with progestins shows promise for a sustained reduction of testosterone levels lasting up to 16 mo in one study (8).…”
Section: Introductionmentioning
confidence: 99%
“…Lower doses of estrogen produce tumor regression without cardiovascular complications but may be less effective than castration. Progestational agents alone are only transiently effective at reducing testosterone (5,6), whereas the recent introduction of antiandrogens (7) or combination of estrogen with progestins shows promise for a sustained reduction of testosterone levels lasting up to 16 mo in one study (8).…”
Section: Introductionmentioning
confidence: 99%
“…Several antiandrogens have been used clinically for the treatment of prostatic cancer [50,. The progestational agents megestrol acetate and cyproterone acetate have had extensive clinical trials [50,54,55]. Cyproterone acetate acts not only by interfering with the receptor binding and nuclear retention of 5 a-dihydrotestosterone, but also at high doses inhibits the release of gonadotropins [60,61].…”
Section: Discussionmentioning
confidence: 99%
“…The same dosing (300 mg IM) was as efficient as 50 mg tablets of cyproterone acetate administered orally twice a day in the treatment of hot flush symptom, a hostile symptom associated with antiandrogen therapy in prostatic cancer patients [204]. Similar studies reported that weekly IM injections of Androcur Depot® yielded the same plasma levels of cyproterone acetate as 50 mg tablets orally administered 4 to 8 times a day (200-400 mg/ day) [205,206]. In other words, one injection of Androcur Depot® (300 mg) is only 21% of the minimal oral dose (200 mg × 7 days) required for weekly management of prostatic cancer.…”
Section: Androcur Depot®mentioning
confidence: 97%